World anthropologies : disciplinary transformations within systems of power. - Ribeiro, Gustavo Lins; Escobar, Arturo (Wenner-Gren international symposium series, 2006)
Since its inception, anthropology's authority has been based on the assumption that it is a unified discipline emanating from the West. In an age of heightened globalization, anthropologists have failed to discuss consistently the current status of their practice and its mutations across the globe. World Anthropologies is the first book to provoke this conversation from various regions of the world in order to assess the diversity of relations between regional or national anthropologies and a contested, power-laden Western discourse.